2007
DOI: 10.1590/s0004-27302007000800024
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy and radiosurgery for Cushing's disease

Abstract: Patients with residual or recurrent Cushing's disease receive external beam radiotherapy (RT) with the aim of achieving long-term tumour control and normalization of elevated hormone levels. Treatment is given either as conventional radiotherapy using conformal techniques or as stereotactic radiotherapy, which is either used as fractionated treatment (SCRT) or as single fraction radiosurgery (SRS). We describe the technical aspects of treatment and report a systematic review of the published literature on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…However, no study has definitely demonstrated a clear correlation between these conditions and a worse outcome of SRT. No correlation between change in tumor volume and hormone response to GK has been described (282,351). The absence of hormone-suppressive medication at the start of GK seems to be associated with a higher likelihood of and earlier remission (328,334,342,343,346).…”
Section: Predictive Factors For the Outcome Of Radiotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…However, no study has definitely demonstrated a clear correlation between these conditions and a worse outcome of SRT. No correlation between change in tumor volume and hormone response to GK has been described (282,351). The absence of hormone-suppressive medication at the start of GK seems to be associated with a higher likelihood of and earlier remission (328,334,342,343,346).…”
Section: Predictive Factors For the Outcome Of Radiotherapymentioning
confidence: 99%
“…a. Hypopituitarism. The main hormonal consequence of pituitary radiotherapy is hypopituitarism (one or more hormone deficiencies), which seems to be mediated by hypothalamic-pituitary damage in the case of CRT, and by direct damage to the pituitary gland and/or pituitary stalk in the case of SRT (282,351,354,355). Actually, the incidence of hypopituitarism attributable to pituitary radiotherapy is difficult to ascertain because persistent hypercortisolism, pituitary mass effects, and prior pituitary surgery beyond radiation therapy may lead to a deficiency of pituitary function (1, 2, 7, 84 -88, 264 -270, 279 -290).…”
Section: Safety Of Radiotherapymentioning
confidence: 99%
“…Another option involves stereotactic radiosurgery ('g-knife') as a single dose delivered through multiple portals [22]. The dose used in g-knife surgery is 18-24 Gy.…”
Section: Radiotherapymentioning
confidence: 99%
“…Several studies analyzing the outcomes of conventional RT report tumor control in 93-100% of patients at a median follow-up of 8 years (3.5-12.4 years) and normalization of cortisol levels in 46-84% of patients in the same follow-up time [22,[24][25][26]. Data related to the results of radiosurgery are claimed to show significantly shorter median follow-up time of 45 months with comparable tumor control in 94% of patients and hormonal normalization achieved in 48% in 6-36 months' time [27][28][29], but no head-to-head comparison of conventional versus radiosurgical RT has been performed.…”
Section: Review | Juszczak and Grossmanmentioning
confidence: 99%
“…Nelson syndrome was originally reported in 1960 when Nelson et al 107 described hyperpigmentation after bilateral adrena- 108 These adenomas tend to be more aggressive in nature, are often associated with extrasellar extension, and thus are more difficult to cure. 56 There have been few studies investigating the role of RT in the treatment of Nelson syndrome, as surgery is often complex given the typical brisk growth of these adenomas.…”
Section: Nelson Syndromementioning
confidence: 99%